International Unions and the Canadian left - Penner, Norman (Imperialism, Nationalism, and Canada: Essays from the Marxist Institute of Toronto, 1977)
Discusses the growth of "international" (i.e., American) unions operating in Canada and the impact on the Canadian labour movement of the bitter divide between socialists and communists. Concludes that the growth of US investment in Canada and US domination of many aspects of Canadian life raises important questions for the Canadian left regarding an independent trade union movement.
Keywords: Canada; Canada Conditions économiques 1945-; Canada Conditions économiques 1971-; Canada Economic conditions 1945-; Canada Economic conditions 1971-1991; Economic history; Nationalism; Nationalism Canada; Nationalisme Canada; Since 1945; Socialism; Socialism Canada; Socialisme Canada